Microvascular breast reconstruction and thromboembolic events in patients on hormone therapy: Audit of practice from a tertiary referral centre. Issue 5 (May 2021) - Samaras, S.; Ashfield, S.; Ali, S.F.; Fopp, L.J.; Benson, J.R.; Malata, C.M.
Abstract: Introduction: Hormonal therapy with tamoxifen and aromatase inhibitors reduces breast cancer recurrence and mortality but represents a risk factor for thromboembolic events. Therefore, most surgeons discontinue hormonal agents before microvascular surgery and for a variable period thereafter. There are no guidelines regarding when therapy should be stopped (preoperatively) or when it should be resumed (post-operatively). We, therefore, audited our hospital practice with the objective of making recommendations for microvascular breast reconstruction patients. Patients and methods: A review was performed of all free flap breast reconstructions between 2014 and 2019. Patients were classified according to hormone medication status at operation. Timings of drug cessation and recommencement were recorded. Thrombotic events, namely flap microvascular thrombosis, deep vein thrombosis, superficial vein thrombosis and pulmonary embolism, were compared. Results: A total of 240 patients had 275 free flaps over five years with 36 receiving hormone therapy within one month prior to surgery, which was discontinued 8.5 days (range: 0–28 days) before surgery. Intraoperative microvascular thromboses (HT 2.0%, NHT 0%, and p  = 0.869) and post-operative microvascular complications/flap re-explorations (HT 6.6%, NHT 0%, and p  = 0.234) were comparable between the two groups. Systemic venous thromboembolic events were also similar (HT 8.3%, NHT 6.1%, and p  = 0.893). Age, BMI, smoking status and preoperative chemotherapy did not influence the incidence of thrombotic complications. Conclusion: Hormone therapy did not significantly increase the risk of thromboembolic events. Despite the widespread practice of withholding it for 2 weeks prior to reconstructive surgery, this study does not support such practice being beneficial in terms of thromboembolic events and flap viability. Large-scale trials are needed to establish definitive protocols.